ASSOCIATION BETWEEN VISUAL FUNCTION AND SUBRETINAL DRUSENOID DEPOSITS IN NORMAL AND EARLY AGE-RELATED MACULAR DEGENERATION EYES. Issue 7 (July 2017) - Neely, David; Zarubina, Anna V.; Clark, Mark E.; Huisingh, Carrie E.; Jackson, Gregory R.; Zhang, Yuhua; McGwin, Gerald; Curcio, Christine A.; Owsley, Cynthia
Abstract : Purpose: To examine the association between subretinal drusenoid deposits (SDDs) identified by multimodal retinal imaging and visual function in older eyes with normal macular health or in the earliest phases of age-related macular degeneration (AMD). Methods: Age-related macular degeneration status for each eye was defined according to the Age-Related Eye Disease Study (AREDS) 9-step classification system (normal = Step 1, early AMD = Steps 2–4) based on color fundus photographs. Visual functions measured were best-corrected photopic visual acuity, contrast and light sensitivity, mesopic visual acuity, low-luminance deficit, and rod-mediated dark adaptation. Subretinal drusenoid deposits were identified through multimodal imaging (color fundus photographs, infrared reflectance and fundus autofluorescence images, and spectral domain optical coherence tomography). Results: The sample included 1, 202 eyes (958 eyes with normal health and 244 eyes with early AMD). In normal eyes, SDDs were not associated with any visual function evaluated. In eyes with early AMD, dark adaptation was markedly delayed in eyes with SDDs versus no SDD (a 4-minute delay on average), P = 0.0213. However, this association diminished after age adjustment, P = 0.2645. Other visual functions in early AMD eyes were not associated with SDDs. Conclusion: In a study specifically focused on eyes in normal macular health and in the earliest phases of AMD, early AMD eyes with SDDs have slower dark adaptation, largely attributable to the older ages of eyes with SDD; they did not exhibit deficits in other visual functions. Subretinal drusenoid deposits in older eyes in normal macular health are not associated with any visual functions evaluated. Abstract : Eyes in the earliest phase of age-related macular degeneration with subretinal drusenoid deposits have slower dark adaptation than early age-related macular degeneration eyes without subretinal drusenoid deposits, largely attributable to the more advanced age of these patients.